Effects of Food Plants of Host Herbivores on Development of a Midgut-Resident Tachinid Parasitoid, Compsilura concinnata (Diptera: Tachinidae), and Two Hemocoel-Resident Parasitoids. (1st March 2014) - Ichiki, Ryoko T; Tabata, Jun; Nakahara, Yuichi; Kainoh, Yooichi; Nakamura, Satoshi
Abstract: The tachinid fly Compsilura concinnata (Meigen) parasitizes insect herbivores throughout the larval period and develops in the midgut. Because the fly larva is directly exposed to the host's gut contents, including nutrients and toxic allelochemicals in the plants eaten by the host, it may be more susceptible to variation in the chemistry of the host's food plants. To evaluate this potential disadvantage of midgut parasitism, we compared the influence of foods of the lepidopteran host Mythimna separata (Walker) on the development of endoparasitoids between C. concinnata and two other species, the tachinid Exorista japonica Townsend and the braconid Cotesia kariyai (Watanabe), whose larvae develop in the host's hemocoel. When the parasitized hosts consumed one of four kinds of plants, all three parasitoid species showed a higher survival, a larger body size, and faster development on two natural food plants (maize and sorghum) than on two alternative foods (kidney bean and Japanese radish). Our results suggest that the development of C. concinnata during midgut parasitism was affected by the host's food species, but that the effects did not differ from those for endoparasitoids with hemocoel parasitism.